Potential of methanol extracts of Nephelium lappaceum (Sapindaceae) and Hyphaene thebaica (Arecaceae) as adjuvants to enhance the efficacy of antibiotics against critical class priority bacteria - Armel Jackson Seukep; Fula Mabel Tamambang; Valaire Yemene Matieta; Helene Gueaba Mbuntcha; Francis Desire Tatsinkou Bomba; Victor Kuete; Lucy M. Ayamba Ndip (PLoS ONE, 2025)
Botanicals have shown promise in mitigating antibiotic resistance in bacteria. This study examined the efficacy of methanolic extracts from two food plants (Nephelium lappaceum and Hyphaene thebaica), alone and in combination with antibiotics, against critical class priority bacteria, including multi-drug resistant (MDR) strains and clinical isolates of Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterobacter aerogenes, and Escherichia coli. The herbals underwent testing using a 96-well microplate serial dilution technique before being analyzed for their effects on bacterial cell membrane integrity and H+-ATPase-mediated proton pumping. Phytochemical analysis was carried out using established techniques. The bioactive extracts displayed very good to weak antibacterial activities (128 ≤ MIC ≤ 2048 μg/mL). The bark, leaf, and peel extracts of N. lappaceum were found to be effective against all studied MDR bacteria. N. lappaceum leaf extract exhibited the best activity (128 ≤ MIC ≤ 1024 μg/mL on all studied MDR bacteria). Interestingly, all MBC/MIC ratios calculated were ≤ 4, suggesting bactericidal activities. N. lappaceum leaf extract has shown significant inhibition of bacterial H+-ATPase-mediated proton pumping and changes in the cell membrane integrity, suggesting possible modes of action. N. lappaceum (leaves and peels) and H. thebaica (fruits) extracts demonstrated a notable potential to synergize with tetracycline, vancomycin, imipenem, ciprofloxacin, and cefixime (up to 8-fold reduction of the antibiotic’s MIC was recorded). N. lappaceum leaves and peels, and fruits of H. thebaica significantly improved the efficacy of all antibiotics tested against K. pneumoniae ATCC11296 at MIC/2. Similar effects were observed against P. aeruginosa PA01 and E. coli AG100, respectively, with leaves and peels of N. lappaceum. No antagonistic interactions were recorded. Qualitative phytochemical screening revealed the presence of tannins, phenols, and saponins in all test extracts. The findings of this study are promising and suggest that N. lappaceum and H. thebaica can be used either for direct action on bacteria or to revitalize outdated antibiotics that are gradually losing their potency due to resistance.